The Effectiveness of Manipulative Motion Skills Development through Game Activities in Elementary School Students Aged 10-12 Years - Edi Setiawan; Bahtiyar Heru Susanto; Dani Sulistiantoro (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The study purpose was to determine the effectiveness of using games in developing students' manipulative motion skills for elementary school students aged 10-12 years. Materials and methods. The study used a quasi-experimental design, consisting of 48 upper-class students divided into a control group and an experimental group. This research was conducted in Koroulon and Jaten elementary schools (Indonesia). Manipulative motion skills tests are given as pre-test and post-test. To analyze the data, MANOVA were used at a significance level of 0.05. The results showed that the experimental group students had higher scores on both dependent variables than the control group. This suggests that manipulative play significantly improved the experimental group of manipulative motion skills compared to the students in the control group. The conclusions in this study, show that the use of games is very effectively used in developing manipulative motion skills of elementary school students aged 10-12 years.